Pembelajaran IPA Berbasis Budaya Lokal melalui Inkuiri Terbimbing pada Konsep Sifat dan Perubahan Wujud Benda - Eva Alviani (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2022)
The delivery of learning with cultural media has an important role in achieving science learning objectives in elementary schools. In achieving the learning objectives, cultural teaching media are needed that are in harmony with the learning materials, namely the Nature and Changes in the Shape of Objects. The cultural media used must be in line with the teaching objectives to be achieved and the learning model used. However, in practice, science learning related to local culture is still very rarely practiced in elementary schools. The use of hawu cultural media, Sundanese dodol aci, and peuyeum Sampu are used as learning media for science based on local culture on the concept of Nature and Changes in Shapes of Objects. The research objectives are (1) to find out the local culture-based science learning process through guided inquiry on the concept of Nature and Changes in Shape of Objects in grade 5 SDN 4 Cihikeu. (2) knowing the improvement of post-study science in understanding the material properties and changes in the shape of objects in grade 5 SDN 4 Cihikeu based on local culture guided inquiry model. The research approach used is a qualitative approach. The methodology used is the classroom action research method. The data analysis technique is in the form of process analysis and teaching outcomes in the first and second cycles using different cultural media. While the data collection technique used is a test in the form of post-test questions, and non-test in the form of observation sheets for teacher and student activities, and field notes. The results showed that the local culture of Hawu, Sundanese dodol aci, and Peuyeum Sampeu can be effective science learning media used with a guided inquiry model.